Qur’an Law’s Perspectives: Surah Al-Baqarah Verse 83 in Early Childhood Education - Nur Rofiq; Titik Mus'idah (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
Children in early childhood is the golden age in a completely human life, they start to sense the environment and ready to receive the education. They ready to get an enhancement of physical function and their psychic is ready to respond and actualized. Problem; 1. How is the concept of Early Childhood Education in the interpretation of the Qur’an Surah Al-Baqarah verse 83? 2. How is the actualizing of Early Childhood Education in the interpretation of the Qur’an Surah Al-Baqarah verse 83? This research aims to analyze the concept and actualization of Early Childhood Education in the interpretation of Surah Al-Baqarah verse 83. The research method is a literature study that based on the book research, notes, and the result of previous research, magazine, and journal. The primary source is Qur’an especially in Surah Al-Baqarah verse 83 and the Prophet’s hadith about Early Childhood Education. The secondary source is the interpretation of the Qur’an about Early Childhood Education and relevant books. Based on the results of the study it found that in Early Childhood Education based on the Qur'an of Surah Al-Baqarah verse 83. Students must be inculcated in an attitude of keeping promises, worshiping God, doing good to parents, doing good with relatives, do good to orphans, say good words to fellow human beings, establish prayer, give alms and not break promises. Kata Kunci: Al-Baqarah verse 83; Early Childhood Education; PAUD. AbstrakTujuan penelitian yaitu untuk mengurai tema konsep dan aktualisasi Pendidikan Anak Usia Dini (PAUD) dalam tafsir Al-Qur’an Surat Al-Baqarah ayat 83. Metode penelitiannya studi kepustakaan (library research) yaitu penelitian berbasis buku, baik berupa buku catatan, hasil penelitian terdahulu, majalah, artikel dan jurnal. Sumber primernya Al-Qur’an khususnya Surat Al-Baqarah ayat 83 dan Hadist Nabi yang berkaitan Pendidikan Anak Usia Dini (PAUD). Sumber sekundernya tafsir Al-Qur’an tentang Pendidikan Anak Usia Dini (PAUD) dan buku yang berkaitan. Berdasarkan hasil penelitian ditemukan bahwa pada Pendidikan Anak Usia Dini (PAUD) berdasarkan Al-Qur’an Surat Al-Baqarah ayat 83 maka peserta didik harus ditanamkan sikap selalu menepati janji, menyembah Allah, berbuat baik terhadap orang tua, berbuat baik dengan kaum kerabat, berbuat baik kepada anak yatim, mengucapkan perkataan yang baik kepada sesama manusia, mendirikan sholat, mengeluarkan zakat dan tidak mengingkari janji Kata Kunci: Sumber Hukum; Al-Baqarah: 83, PAUD.